Construction of a novel inducible expression vector for Lactococcus lactis M4 and Lactobacillus plantarum Pa21 - Maidin, Mohd Shawal Thakib; Song, Adelene Ai Lian; Jalilsood, Tannaz; Sieo, Chin Chin; Yusoff, Khatijah; Abdul Rahim, Raha (Elsevier, 2014)
A vector that drives the expression of the reporter gusA gene in both Lactobacillus plantarum and Lactococcus lactis was constructed in this study. This vector contained a newly characterized heat shock promoter (Phsp), amplified from an Enterococcus faecium plasmid, pAR6. Functionality and characterization of this promoter was initially performed by cloning Phsp into pNZ8008, a commercial lactococcal plasmid used for screening of putative promoters which utilizes gusA as a reporter. It was observed that Phsp was induced under heat, salinity and alkaline stresses or a combination of all three stresses. The newly characterized Phsp promoter was then used to construct a novel Lactobacillus vector, pAR1801 and its ability to express the gusA under stress-induced conditions was reproducible in both Lb. plantarum Pa21 and L. lactis M4 hosts.